Mielorradiculopatia esquistossomótica: estudo comparativo com mielite por HTLV-1 (HAM/TSP) - Fidelis, Thiago André Alves (2013)
Schistosomiasis mansoni represents one of the largest and most serious public health problems in Brazil, being endemic in 19 units of the Brazilian federation, most of them in brazilian Northeast region. Alagoas, state of Brazil, has 69% of its municipalities an endemic area of schistosomiasis, with mortality attributed to that disease. In that state, over two and a half million people are living under the risk of that disease in 70 cities. One form of the disease, the Schistosomal Myeloradiculopathy (SMR) is considered most serious form. This study proposes to evaluate the clinical and laboratory results of patients with SMR, and to compare it with Human T-Lymphotropic Virus Type I Associated Myelopathy/Tropical Spastic Paraparesis (HAM/TSP) patients` results, attended at two public hospitals in Maceió, capital of Alagoas, on the period of 2008-2011. Three hundred forty-six records were examined, of which 23 (6.64%) were cases of people with SMR, with higher rates for men aged 20-39 years old. The cases of HAM/TSP (19), represented 5,49% of the records, predominant in women, aged between 40-60 years old. The present study indicated significant differences in eight of 16 variables evaluated (paraplegia, sexual dysfunction, spasticity on lower limbs, bladder retention, sagging of the lower limbs, no-reflections on lower limbs and hypoesthesia tactile/thermal on lower limbs), listing symptoms between SMR and HAM/TSP. Abnormalities were observed in 100% of patients that used Magnetic Resonance Imagining, accusing myelitis as diagnosis, prevailing on thoracic region (T11-T12). Eosinophil levels in Cerebro Spinal Fluid in patients with SMR accused average of 2.8%. Differences was observed in results relating Cerebro Spinal Fluid analysis between patients with SMR and HAM/TSP for glucose and protein levels, and lymphocytic pleocytosis. The diagnosis of SMR must to involve epidemiological, clinical, laboratory and imagining aspects.